Networked Scaffolding: Seeking Support in workplace learning contexts - Santos, Patricia; Cook, John; Treasure-Jones, Tamsin; Kerr, Micky; Colley, Joanna (Proceedings of the International Conference on Networked Learning, 2014)
The overall objective of WP2 (work-package of Learning Layers, the European research project in Technology Enhanced Learning) is one of designing solutions for scaffolding learning in networks. Specifically, this means developing designs and tools to scaffold help seeking learning in a networked workplace context. This paper presents the conceptual research of the 1st year (WP2). We provide a theoretical discussion around the concept ’Networked Scaffolding’, and illustrate our research ideas through a specific case study ’Seeking Support’ in the Healthcare context. Social Network Technologies, the focus of this paper, scale personal interactions by extending and augmenting the reach of personal networks, and form a central part of the Learning Layers integrated systems view on scaffolding informal learning at the workplace. In this context, semantic technologies are used to scale the representation and generation of meaning. In particular, we focus our study on an illustrative case of the Healthcare context in UK. Specifically, we are interested in studying how professional exchange trusted learning opinions, becoming more the norm in professional settings, developed around intentional networks that are constantly managed and reconstituted as Personal Learning Networks. The significance of mobile technology to enable and support these processes is an important aspect of this research. Indeed, there is still a lack of research in this field (i.e. scaffolding networked learning on a large scale for work-based learning). However, some authors such as Sandars, Langlois, & Waterman (2007) provide some very useful insights into online collaborative learning within Healthcare that is particularly helpful for developing theory around mobile technologies that healthcare professionals will be using within this research. Regarding the topic of Social Network Sites (SNS), we elaborate the concept of "Networked Scaffolding" with the aim of understanding how scaffolding has to be applied in SNSs with a work-based context. For this reason, in this paper we review how technology is currently being used in work-based learning contexts and the main related approaches. In the next section we present and discuss the theoretical and technological foundations related to the Networked Scaffolding concept proposed. Then, we show the application of our ideas through a design team called PANDORA which aims to scaffold seeking support in the Healthcare context. A summary of the co-design activities and the preliminary outputs are presented. Finally, we conclude with next steps to be done in future work